Inheritance Disputes Over Assets Still Under Debt Collateral Status from an Islamic Law Perspective - Januaris, Fadli; Adriaman, Mahlil (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
Inheritance disputes involving assets under debt collateral status present unique challenges in the context of Islamic law, where debt repayment takes precedence over the distribution of inheritance. In Islamic banking, assets pledged as collateral (marhun) are considered the debtor's property but remain under the creditor's claim until the associated debt is fully paid. This creates legal and ethical complexities when the debtor passes away, as the heirs' right to inheritance may conflict with the creditor's right to the pledged asset. This study examines these disputes from an Islamic law perspective, focusing on the balance between fulfilling financial obligations and ensuring justice for heirs. The research analyzes relevant principles in Islamic inheritance law, including the prioritization of debt repayment and the distribution of remaining assets to heirs. It also evaluates the regulatory framework of Islamic banking, which often introduces contractual obligations affecting inheritance claims. Case studies are used to illustrate practical scenarios and highlight potential conflicts between creditors and heirs. The findings reveal that the resolution of such disputes requires a harmonization of traditional Islamic jurisprudence with contemporary banking practices. Proposed solutions include transparent debt documentation, equitable mechanisms for settling debts from the estate, and clear guidelines for managing collateralized assets in inheritance cases. By addressing these issues, this study contributes to the development of legal frameworks that uphold sharia principles, ensuring justice and fairness for all parties while maintaining the integrity of financial transactions and inheritance systems.